Encapsulation of plant growth promoting Rhizobacteria—prospects and potential in agricultural sector: a review. (26th November 2019) - Vejan, Pravin; Khadiran, Tumirah; Abdullah, Rosazlin; Ismail, Salmah; Dadrasnia, Arezoo
Abstract: Plant growth promoting rhizobacteria (PGPR) are a group of bacteria that can enhance plant growth. In fact, PGPR are biologically unstable and the bacteria activity degrades over time due to environmental factors, survival rate in soils, the compatibility with the crop and the interaction ability with the indigenous microflora in soil. Therefore, the utilization of PGPR as plant growth promoter agent is a major challenge in the agricultural sectors because of their bioactivity degradation needs to be inhibited to maximize its function as a plant growth promoter. The application of delivery system based on encapsulation technology shows a promising technique to store and deliver PGPR. However, the task to find the appropriate PGPR encapsulation method is the most challenging for agricultural industry. In addition, the lack of knowledge on the action mechanism of encapsulated PGPR, physico-chemical properties and their survival in the environment are the many challenges need to be addressed. In the present review, the encapsulation technology of PGPR and its properties have been reviewed in detail. Moreover, the remaining technical challenges of encapsulation systems including insignificant stabilization of PGPR, instability of the environmental and difficulty of their preparation are also extensively discussed here.